Histopatologi Insang dan Hati Benih Ikan Nila Hitam (Oreochromis niloticus) Hasil Pembenihan di Batuplat, Kota Kupang, Nusa Tenggara Timur - Shobikhuliatul Jannah Juanda; Aisyah Lukmini; Yusuf Kamlasi; Ion Tarsardo Sianturi (Juvenil, 2026)
This study aims to determine the histopathological of the gill and liver of black tilapia fingerlings that produced by farmers in Batuplat, Kupang City. Eighty sample fingerlings taken randomly from the hatchery and brought to the laboratory for measurement of length and weight, observation of morphological abnormalities, gill and liver were taken for histological preparation. Histopathological analysis were carried out by microscopic observation of each organ and then compared with the image obtained from relevant journal references. In this study, the morphological abnormality is the presence of wounds (ulcer) on the body such as peeling scales, ripped pinna cudalis pinna dorsalis, flaky pinna caudalis and dark body color. The gill’s damage tissue was proliferation of mucus cell, primary and secondary lamella edema, hyperplasia of primer and secondary lamella, fusion of secondary lamella, congestion of primary lamella, hypertropi of secondary lamella, primary and secondary lamella necrosis and the presence of parasites. While the liver showed the presence of a melano macrophage center (MMC), hemorage, congestion, fibrosist, sinusoidal congestion, the presence of hemosiderin, lipid degeneration, vacuola and necrosis. Further research is recommended to identify parasites and diseases in black tilapia fingerling at the same location.